Chemical composition, in vitro antioxidant activity and α-glucosidase inhibitory effects of the essential oil and methanolic extract of Elsholtzia densa Benth. - Xue Xuanji; Guo Zengjun; Zhang Hui; Liu Xia; Luo Jun; Li Dandan; Li Jun (Natural Product Research, 2016)

A polydnaviral genome of Microplitis bicoloratus bracovirus and molecular interactions between the host and virus involved in NF-κB signaling - Dong-Shuai Yu; Ya-Bin Chen; Ming Li; Ming-Jun Yang; Yang Yang; Jian-Sheng Hu; Kai-Jun Luo (Archives of Virology, 2016)

Nematode‐trapping fungi and fungus‐associated bacteria interactions: the role of bacterial diketopiperazines and biofilms on Arthrobotrys oligospora surface in hyphal morphogenesis - Lei Li; Min Yang; Jun Luo; Qing Qu; Ying Chen; Lianming Liang; Keqin Zhang (Environmental Microbiology, 2016)
Summary In soil, nematode‐trapping fungi and bacteria often share microhabitats and interact with each other, but effects of fungus‐associated bacteria on its trap formation are underestimated. We have ascertained the presence of Stenotrophomonas and Rhizobium genera associated with A. oligospora GJ‐1. After A. oligospora GJ‐1 without associated bacteria (cured Arthrobotrys ) was co‐cultivated with Stenotrophomonas and its supernatant extract, microscopic study of hyphae from co‐cultivation indicated that bacterial biofilm formation on hyphae was related to trap formation in fungi and Stenotrophomonas supernatant extract. Four diketopiperazines (DKPs) were purified from Stenotrophomonas supernatant extract that could not induce traps in the cured Arthrobotrys . When cured Arthrobotrys was cultured with Stenotrophomonas and one of DKPs, polar attachment, bacterial biofilms on hyphae and trap formation in fungi were observed. After cured Arthrobotrys with bacterial biofilms was consecutively transferred several times on nutrient poor medium, trap formation disappeared with the disappearance of bacterial biofilms on hyphae. DKPs could facilitate chemotaxis of Stenotrophomonas towards fungal extract which was suggested to contribute to bacterial biofilms on hyphae. Furthermore, when cured Arthrobotrys was cultured with Stenotrophomonas and DKPs in soil, trap formation in fungi and bacterial biofilms on hyphae were also observed, and the fungal activity against nematode was enhanced.

Ethanol Increases Mechanical Pain Sensitivity in Rats via Activation of GABAA Receptors in Medial Prefrontal Cortex - Kai-Wen Geng; Ting He; Rui-Rui Wang; Chun-Li Li; Wen-Jun Luo; Fang-Fang Wu; Yan Wang; Zhen Li; Yun-Fei Lu; Su-Min Guan; Jun Chen (Neuroscience Bulletin, 2016)

Inhibition of the oxidative stress-induced miR-23a protects the human retinal pigment epithelium (RPE) cells from apoptosis through the upregulation of glutaminase and glutamine uptake - Dan-dan Li; Bin-wu Zhong; Hai-xia Zhang; Hong-yan Zhou; Jie Luo; Yang Liu; Gui-chun Xu; Chun-sheng Luan; Jun Fang (Molecular Biology Reports, 2016)

Permeability of novel 4′-N-substituted (aminomethyl) benzoate-7-substituted nicotinic acid ester derivatives of scutellarein in Caco-2 cells and in an in vitro model of the blood-brain barrier - Yu Ou; Min Luo; Yong-Xi Dong; Hang Su; Xiao-Zhong Fu; Yu-Feng Cha; Shun Zhang; Yong-Long Zhao; Yong-Jun Li; Yong-Lin Wang (Medicinal Chemistry Research, 2016)

NK cells contribute to persistent airway inflammation and AHR during the later stage of RSV infection in mice - Xiaoru Long; Jun Xie; Keting Zhao; Wei Li; Wei Tang; Sisi Chen; Na Zang; Luo Ren; Yu Deng; Xiaohong Xie; Lijia Wang; Zhou Fu; et al. (Medical Microbiology and Immunology, 2016)

Greenhouse gas emissions in a spring wheat–field pea sequence under different tillage practices in semi-arid Northwest China - Stephen Yeboah; Renzhi Zhang; Liqun Cai; Min Song; LingLing Li; Junhong Xie; Zhuzhu Luo; Jun Wu; Jun Zhang (Nutrient Cycling in Agroecosystems, 2016)

PCI-24781 can improve in vitro and in vivo developmental capacity of pig somatic cell nuclear transfer embryos - Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Yu-Chen Zhang; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Xi-Jun Yin; Jin-Dan Kang (Biotechnology Letters, 2016)

Cerebral blood flow changes in hemodialysis and peritoneal dialysis patients: an arterial-spin labeling MR imaging - Xiao Lu Jiang; Ji Qiu Wen; Long Jiang Zhang; Gang Zheng; Xue Li; Zhe Zhang; Ya Liu; Li Juan Zheng; Long Wu; Hui Juan Chen; Xiang Kong; Song Luo; et al. (Metabolic Brain Disease, 2016)

Efficient biodegradation of phenanthrene by a novel strain Massilia sp. WF1 isolated from a PAH-contaminated soil - Haizhen Wang; Jun Lou; Haiping Gu; Xiaoyan Luo; Li Yang; Laosheng Wu; Yong Liu; Jianjun Wu; Jianming Xu (Environmental Science and Pollution Research, 2016)

Three duplication events and variable molecular evolution characteristics involved in multiple GGPS genes of six Solanaceae species - FENG LI; CHUNYANG WEI; CHAN QIAO; ZHENXI CHEN; PENG WANG; PAN WEI; RAN WANG; LIFENG JIN; JUN YANG; FUCHENG LIN; ZHAOPENG LUO (Journal of Genetics, 2016)

Sodium Para-aminosalicylic Acid Protected Primary Cultured Basal Ganglia Neurons of Rat from Manganese-Induced Oxidative Impairment and Changes of Amino Acid Neurotransmitters - Shao-Jun Li; Yong Li; Jing-Wen Chen; Zong-Xiang Yuan; Yu-Huan Mo; Guo-Dong Lu; Yue-Ming Jiang; Chao-Yan Ou; Fang Wang; Xiao-Wei Huang; Yi-Ni Luo; Shi-Yan Ou; et al. (Biological Trace Element Research, 2016)

Involvement of NADPH oxidases and non-muscle myosin light chain in senescence of endothelial progenitor cells in hyperlipidemia - Ting-Bo Li; Jie-Jie Zhang; Bin Liu; Wei-Qi Liu; Yan Wu; Xiao-Ming Xiong; Xiu-Ju Luo; Qi-Lin Ma; Jun Peng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

PI3K/Akt/FoxO3a signaling mediates cardioprotection of FGF-2 against hydrogen peroxide-induced apoptosis in H9c2 cells - Mi-Hua Liu; Guo-Hua Li; Li-Jun Peng; Shun-Lin Qu; Yuan Zhang; Juan Peng; Xin-Yuan Luo; Heng-Jing Hu; Zhong Ren; Yao Liu; Hui Tang; Lu-Shan Liu; et al. (Molecular and Cellular Biochemistry, 2016)

Clinical validation of a novel real-time human papillomavirus assay for simultaneous detection of 14 high-risk HPV type and genotyping HPV type 16 and 18 in China - Hui Yang; Lie-Jun Li; Long-Xu Xie; Zhao-Yun Luo; Min Lu; Min Lin; Xiang-bin Zheng; Yue Huang; Li-Ye Yang (Archives of Virology, 2016)

Location- and Subunit-Specific NMDA Receptors Determine the Developmental Sevoflurane Neurotoxicity Through ERK1/2 Signaling - Wen-Yuan Wang; Li-Jie Jia; Yan Luo; Hong-Hai Zhang; Fang Cai; Hui Mao; Wei-Cai Xu; Jun-Biao Fang; Zhi-You Peng; Zheng-Wen Ma; Yan-Hong Chen; Juan Zhang; et al. (Molecular Neurobiology, 2016)

Concomitant coronary and renal revascularization improves left ventricular hypertrophy more than coronary stenting alone in patients with ischemic heart and renal disease - Hao-jian Dong; Cheng Huang; De-mou Luo; Jing-guang Ye; Jun-qing Yang; Guang Li; Jian-fang Luo; Ying-ling Zhou (Journal of Zhejiang University-SCIENCE B, 2016)

Distinct subcellular localization and potential role of LINE1-ORF1P in meiotic oocytes - Yi-Bo Luo; Li Zhang; Zi-Li Lin; Jun-Yu Ma; Jialin Jia; Suk Namgoong; Qing-Yuan Sun (Histochemistry and Cell Biology, 2016)